The effect of endoscopic vein harvesting in coronary artery bypass surgery - Ran, Jun (J Thorac Dis, 2020)
BACKGROUND: To compare the clinical outcomes, quality of saphenous vein (SV) grafts, and wound complications between endoscopic vein harvesting (EVH) technique and open vein harvesting (OVH) technique in patients with coronary artery bypass graft (CABG) surgery. METHODS: We reviewed one hundred patients with multi-vessel coronary artery disease who underwent elective CABG and agreed to preserve their SV specimens for study. Fifty patients (OVH group) underwent OVH, and the remaining (EVH group) underwent EVH. The median follow-up time was 12 months. Clinical outcomes, 1-year graft patency rates, endothelium integrity of SV grafts and wound complications were assessed. RESULTS: The follow-up time was 12 [12–13] months. Recurrence of angina was observed in 5 patients, with 3 (6.1%) in EVH group and 2 (4%) in OVH group (P=0.68). The endothelium integrity of specimens before distension was similar in both the groups (EVH: 81.1%±6.11% vs. OVH: 80.8%±6.58%, P=0.83). After distension, the endothelium integrity was still similar (EVH: 70.7%±9.73%; OVH: 68.3%±9.60%; P=0.22). Grafts of 5 (11.6%) patients in EVH group were classified as occluded, and 4 (9.8%) patients in OVH group showed occlusion of SV grafts (P=1.0). After day 7, the postoperative leg pain was significantly milder in EVH group than OVH group (1.16±0.76 vs. 2.50±0.91, P<0.01). CONCLUSIONS: These findings suggest that EVH is not associated with worse clinical outcomes or conduit quality. However, it may have advantage in wound healing.